The Influence of Big 4 Audit Firms and Audit Fees on the Communication of Key Audit Matters with the Moderating Role of Audit Committee Financial Expertise - Syofnita, Adillah Abir; Rahman, Annisaa (Dinasti Publisher, 2026)
This study examines the effect of Big 4 audit firms and audit fees on the communication of Key Audit Matters, with audit committee financial expertise as a moderating variable. The study was conducted on companies listed on the Indonesia Stock Exchange during 2022–2024. This research uses a purposive sampling method, resulting in a sample of 501 companies from a population of 930, with a total of 1,503 observations. The analytical method used is negative binomial regression. The results of this study show that Big 4 audit firms have a significant positive effect on both the number of issues and number of words in KAMs. Audit fees do not have a significant effect on the number of KAMs issues but have a significant negative effect on the number of KAMs words. In addition, audit committee financial expertise is able to strengthen the relationship between Big 4 audit firms and both the number of issues and the number of words in KAMs. Conversely, it is not able to moderate the relationship between audit fees and both the number of issues and words in KAMs.